2020
DOI: 10.1039/d0ta01063d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrocatalytic activity and selectivity of glycerol oxidation triggered by nanoalloyed silver–gold nanocages directly grown on gas diffusion electrodes

Abstract: Partial galvanic replacement of silver atoms by those of gold was optimized to fabricate free-standing highly active and selective electrocatalysts for glycerol electrooxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Table S2 summarizes the performance of nanostructured mono-and bi-metallic catalysts for the electrooxidation of glycerol in basic solutions, which have a peak current density of jp = 20-290 mA cm −2 based on the area of the electrode or jp = 0.2-18 A mgAu −1 , and where metal content is fairly high of 16-500 µgAu cm −2 . 20, 28,[53][54][55][56][57][58] Except for few examples of nanoalloynanoporous AuAg 19 and Pt-PtCo, 53,57 it can, therefore, be deduced that the performance of the asfabricated GDE-Au freestanding material is superior to the relevant activities reported in the literature for gold-, palladium-, and platinum-based electrocatalysts. 20, [54][55][56][58][59][60][61][62] To our knowledge, this is the first time a free-standing electrocatalyst made of desert rose-like nanostructured gold has been obtained directly onto carbon fiber electrode and demonstrate high performance towards the glycerol electrooxidation.…”
Section: Performance Comparison With the Commercial Vulcan-au Catalystmentioning
confidence: 94%
See 1 more Smart Citation
“…Table S2 summarizes the performance of nanostructured mono-and bi-metallic catalysts for the electrooxidation of glycerol in basic solutions, which have a peak current density of jp = 20-290 mA cm −2 based on the area of the electrode or jp = 0.2-18 A mgAu −1 , and where metal content is fairly high of 16-500 µgAu cm −2 . 20, 28,[53][54][55][56][57][58] Except for few examples of nanoalloynanoporous AuAg 19 and Pt-PtCo, 53,57 it can, therefore, be deduced that the performance of the asfabricated GDE-Au freestanding material is superior to the relevant activities reported in the literature for gold-, palladium-, and platinum-based electrocatalysts. 20, [54][55][56][58][59][60][61][62] To our knowledge, this is the first time a free-standing electrocatalyst made of desert rose-like nanostructured gold has been obtained directly onto carbon fiber electrode and demonstrate high performance towards the glycerol electrooxidation.…”
Section: Performance Comparison With the Commercial Vulcan-au Catalystmentioning
confidence: 94%
“…This is significantly lower than that of the oxygen evolution reaction (OER, higher than 1.4 V vs RHE), so that the oxidation of those organic compounds instead of water at the anode in electrolyzers is expected to significantly lower the input energy. [18][19][20][21] Also, because the anode reaction only occurs in a potential range well below 1 V vs RHE, carbon fiber papers as support in anode were used in organic-fuelled reactors without concern for their oxidation. 18,22 This emerging research direction constitutes a meaningful option to advance the development of an efficient anode to be associated with the electricity-driven half-cell processes of hydrogen evolution reaction (HER), CO2 reduction reaction (CO2RR), and N2 reduction reaction (N2RR) for the production of valuable fuels and chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…while reducing the noble metal content. [154,155] The alloyed 3d metals can also downshift the d-band center of Pt/Pd atoms, resulting in a weaker bonding to the surface intermediates and/or products thus increasing the stability. [92,156,157] Pt alloys based on Ni, Fe, Co, and Cu have all shown remarkable catalytic performances toward glycerol electro-oxidation, with their mass and specific activities 2-7-fold higher than commercial catalysts.…”
Section: Alloysmentioning
confidence: 99%
“…Presented data were originally reported as follows: PdAuNi nanosponges, [177] Pd-Ru nanocages, [149] Pd-Cu-Pt, [178] PdPt nanowires, [152] PdBi, [179] Pd-CNx/G, [142] PdAg, [163] FeCo@Fe@Pd, [180] PtPdM, [181] PtM nanocubes, [161] PtNi nanorod, [160] PtFe nanowires, [158] PtCo nanowires, [159] PtCu nanoframes, [162] 2D AuCu nanoprisms, [182] Au-P4P/G, [183] AgAu nanocage. [154] oxidation. Further studies showed the interaction of the Bi adatom with the enediol intermediate, driving selectivity toward the most stable isomer dihydroxyacetone (Figure 13).…”
Section: P-block Metalsmentioning
confidence: 99%
See 1 more Smart Citation